Can the Theory of Risk Evaluation and Management Be Applied to Land-use Safety Planning? - Mark Schaerlaekens (Chemical Engineering Transactions)
When a comparison is made between land-use safety policies in different countries or regions, it is quickly apparent how diverse the assessment is made, both between the different sectors and application domains as regions; (1) there are large variations when assessing the acceptability of different risk levels, (2) hazards with large effects but very small probability are sometimes dominating the assessment or completely absent (as they are not considered among the ‘credible’ or ‘representative’ scenario’s) and (3) there appears to be a difference between unacceptable risks according to the followed policy and the appreciation of the same risk by part of the population. Further, a lack of uniform and consistent standards for determining the nature of risks and assessing their magnitude is notable and confusing. At first glance, the various actors involved notice inconsistencies and feel the need to eliminate these inconsistencies. However, the theory of risk evaluation and risk management reveals that (sometimes) such “irrationalities” can be made completely understandable and rational. In this paper, some concepts from risk theory are briefly introduced and applied to risk policy in spatial planning. A primary principle is that of the relative unacceptability of risk. When applied correctly, this helps to set ambitious goals in land use safety planning, where the potential of land use planning (LUP) to avoid unnecessary risk in a very robust way can be fully utilized. At the same time, accepting the relativeness of unacceptability helps to place risks in other domains, which are sometimes of a different order of magnitude, in a different context. Most of us would in most circumstances see the loss of 50 human lives as catastrophic, but for a general in WWI it was apparently a negativity well within the ordinary range — a mere pinprick easily taken in stride. When the relative acceptability of risk is neglected for being as consistent as possible across policy domains, one runs the risk of imposing artificial standards of theoretical rationality that conflict with accepted factual practices or intuitions. The discussion on the applicability of the FN criteria for industrial installations used in the Netherlands to the off-sites risks from Schiphol airport, is a good example of this theoretical rationality that conflicts with accepted factual practices. Risk theory confirms a possible outcome that criteria can be inapplicable. Furthermore, the risk aversion, which is present in some land-use safety planning criteria has been scrutinized in the context of the sequential priority order of the various principles of rational risk management: (1) reject extremely unlikely (“unrealistic”) possibilities! (2) avoid catastrophes (3) maximize expected values (by minimizing loss of life). This paper attempts to show the gap between risk theory and land-use safety planning practices, that should be bridged. It is the ambition of the author that the theoretical underpinnings of risk theory, applied to land use safety planning criteria, can contribute in setting ambitious and righteous criteria and standards.